Pengaruh Jam Kerja Dan Pengalaman Kerja Terhadap Pendapatan Karyawan (Studi Kasus Pabrik Tahu CNG dan CND) - Ega Ade Kamulalis (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of working hours and work experience on the income of employees at the CNG and CND tofu factories in Solok district. The population of this study as many as 45 people. The sampling technique in this study is total samplingBased on the results of this study, it can be concluded that working hours have a significant effect on employee income, this can be proven by using the t test with a significant value t_count (15.591) > t_table (2.018) and a significant value of 0.000 <0.05. while work experience has no significant effect on employee income, this can be proven by the t test with a significant value t_count (0.541) < t_table (2.018) and a significant value of 0.592> 0.05. Simultaneously working hours and work experience affect employee income, this can be proven by using the f test with the F_count value of 185.792 > 3.22 with a significance value of 0.000 < 0.05. This can also be seen from the R Square value of 0.898 or 89.8% and the remaining 10.2% is influenced by other variables outside this study.